PENGARUH SUBTITUSI TEPUNG TERIGU DENGAN TEPUNG SUKUN (Artocarpus altilis) TERHADAP MUTU KIMIA KUE SEMPRONG - Fitriani Basrin (Jurnal Pengolahan Pangan, 2020)
Breadfruit (Artocarpus altilis) is one of the main fruit producing plants of the Moraceae family. This plant has long been cultivated by the people of Indonesia and even in several countries in the Pacific region such as Fiji, Tahiti, the Samoan Islands, and Hawaii, breadfruit has been used as a traditional staple food. The consumption of breadfruit is generally still limited as a snack and a vegetable and as an alternative food source, breadfruit is proven to have a high nutritional content. The purpose of this study was to determine the effect of substitution of wheat flour with breadfruit (Artocarpus altilis) on the chemical quality of semprong cake or egg roll. The treatment design in this research on the substitution of wheat flour with breadfruit flour (Artocarpus altilis) on the chemical quality of semprong cakes, namely: P0 (100 grams of wheat flour), P1 (75 grams of wheat flour + 25 grams of breadfruit flour), P2 (50 grams of wheat flour + 50 grams of breadfruit flour), P3 (75 grams of wheat flour + 25 grams of breadfruit flour), and P4 (100 grams of breadfruit flour). The experimental design used was a randomized randomized design (CRD) with 5 treatments and 4 replications. The results of the proximate analysis test included moisture, ash, fat, protein and carbohydrate content, with an average value of 3.50% water content, 1.07% ash content, 26.97% fat content, 4.21% protein content, and 63.88% carbohydrate content.